Hubungan Kampanye Vaksinasi dengan Sikap Followers untuk Divaksin - Abdullah Mufty Machmud; Ani Yuningsih (Jurnal Riset Public Relations, 2021)
Abstract. Recorded cases of Covid-19 in Indonesia reached 1.6 million (26/04/2021). With the outbreak and the dangerous characteristics of this virus, the Indonesian government has focused on handling the virus as a priority, and efforts to prevent its spread continue to be carried out. One of the programs is a vaccination program for all people in Indonesia. Until now, the vaccination program is still ongoing, and the vaccination program is planned to be completed in March 2022. However, several obstacles occur in expanding the vaccination program to the community, one of which is the reluctance to be vaccinated by individuals for various reasons. In this study, we will discuss the relationship of the campaign carried out by the Indonesian Ministry of Health on Instagram to its followers in relation to attitudes to vaccines. This quantitative study aims to determine how big the relationship between vaccination campaign activities and the attitude of followers to be vaccinated. This study uses the theory of Diffusion of Innovations in guiding the implementation of campaign activities that emphasize campaign actors, message content, and the structure of campaign messages with the attitude of followers to be vaccinated and which will be discussed in the form of attitudes from cognitive, affective, conative aspects. The sample to be studied is 100 active Instagram followers with multistage random sampling technique. The result in this research that there’s a correlation between vaccination’s campaign with followers’s attitude that lead will of getting vaccination. Abstrak. Tercatat kasus Covid-19 di Indonesia mencapai 1.6 juta (26/04/2021). Dengan adanya wabah dan bahayanya karakteristik virus ini, pemerintah Indonesia memfokuskan penanganan virus menjadi sebuah prioritas, upaya pencegahan penyebaranpun terus dilakukan. salah satunya program ialah program vaksinasi untuk seluruh masyarakat di Indonesia. Hingga kini program vaksinasi masih terus berlanjut, dan rencananya program vaksinasi akan selesai pada Maret 2022. Namun beberapa kendala terjadi dalam memperluas program vaksinasi ke masyarakat, salah satunya ialah rasa enggan untuk divaksin yang dimiliki oleh individu dengan berbagai alasan yang dimiliki. Di dalam penelitian ini, akan dibahas tentang hubungan daripada kampanye yang dilakukan oleh kementerian kesehatan RI di Instagram terhadap followersnya terkait dengan sikap untuk vaksin. Penelitian kuantitatif ini bertujuan untuk mengetahui seberapa besar hubungan kegiatan kampanye vaksinasi dengan sikap followers untuk divaksin. Penelitian ini menggunakan teori Diffusi Inovasi dalam memandu penyelenggaraan kegiatan kampanye yang ditekankan pada aktor kampanye, isi pesan, dan struktur pesan kampanye dengan sikap followers untuk divaksin dan yang akan dibahas berupa sikap dari aspek kognitif, afektif, konatif. Sampel yang akan diteliti ialah followers aktif Instagram sebanyak 100 orang dengan teknik multistage random sampling. Hasil penelitian ini menunjukkan bahwa adanya hubungan kampanye vaksinasi kemenkes RI di Instagram dengan sikap followers untuk divaksin.